Suicidal Major Depression in a Healthcare Worker Associated with the COVID-19 Pandemic: A Case Report - Ali Erdoğan; Gizem Pala; Buket Cinemre (Düzce Tıp Fakültesi Dergisi, 2021)
Novel coronavirus disease (COVID-19) pandemic has been affecting the whole world since December 2019. During the pandemic, healthcare professionals are at the forefront of the fight against COVID-19, and many healthcare workers died during this fight. Healthcare workers, who are at the forefront of the pandemic, are under intense mental and physical stress along this period. This disease makes increase psychiatric symptoms for general population and especially in health professionals at pandemic conditions. In particular, the symptoms of burnout, depression, and anxiety have rised significantly. With this case report, we present a physician who had symptoms that started during the COVID-19 pandemic, had depression accompanied by suicidal thoughts, and went into complete remission with electroconvulsive therapy. The mental health effects of healthcare workers who have had COVID-19 are discussed within the frame of this case report.